ANALISIS MOTIVASI BELAJAR TERHADAP HASIL BELAJAR MAHASISWA PADA MATA KULIAH FISIKA DASAR BERDASARKAN GOLONGAN DARAH - Rudi Haryadi (Biodidaktika : Jurnal Biologi dan Pembelajarannya, 2016)
ABSTRACTMotivation is interest of the students for learniing that are driven by the desire to achieve the learning outcomes. The outcomes is an important part of learning. Results of student learning is essentially changed the student behavior which include the areas of cognitive, affective, and psychomotor. Learning outcomes are the result of an interaction act of learning and teaching acts. For a lecturer, teaching acts ends with the evaluation of learning outcomes. In terms of student learning outcomes is the end of the teaching of the peak of the learning process. In the process pembeljaran, learning outcomes can be influenced by internal factors possessed by students, namely blood type. Blood type is a characteristic of blood from an individual because of different types of carbohydrates and protein on the surface of red blood cell membranes. The purpose of this study was to determine the motivation of learning on student learning outcomes on student course Basic Physics based on blood type. The results showed the average learning outcomes from the largest to the smallest are owned by people who have blood type O, A, AB, B. This shows that internal factors influence the process of student learning outcomes.